An aqueous film-coating formulation based on sodium carboxymethyl mungbean starch - Kittipongpatana O.S. (2014)
The preparation of sodium carboxymethyl starch (SCMS) based film-coating agents used for coating of pharmaceutical products, was investigated. A 3% (w/v) solution of sodium carboxymethyl mungbean starch (SCMMS), containing plasticizers such as polyethylene glycol (PEG) and glycerol, was dried at 60°C for 17h. Native mungbean starch paste, prepared in boiling water, was used to form a control film and SCMMS film was employed in the film coating of paracetamol tablets. The talcum,titanium oxide and dye was added in the coating solution containing plasticizer and coating was applied in Thai Coater-15 under influx air temperature of 75°C, and spraying pressure of 400kPa. It was observed that the SCMMS film, without the addition of plasticizers, showed better strength, and texture in comparison of native mungbean starch. Result shows that modification of mungbean starch by carboxylation improve physicochemical properties of native starch.